2022
DOI: 10.3389/fendo.2022.934675
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and cardiovascular morbidity in patients with congenital adrenal hyperplasia

Abstract: Since the introduction of glucocorticoid (GC) replacement therapy, congenital adrenal hyperplasia (CAH) is no longer a fatal disease. The development of neonatal screening programs and the amelioration of GC treatment strategies have improved significantly life expectancy in CAH patients. Thanks to these achievements, CAH patients are now in their adulthood, but an increased incidence of cardiovascular risk factors has been reported compared to general population in this stage of life. The aim of CAH treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…It is believed that metabolic abnormalities in people with CAH are a consequence of the cortisol deficiency, with the subsequent androgen excess [ 58 ], hypercortisolism related to the GC treatment, which mimics iatrogenic hypercortisolism, as well as the underdevelopment of adrenal medulla [ 11 , 59 , 60 ]. Obesity, which is an independent CV risk factor, is the most frequent component of metabolic syndrome in people with CAH [ 61 ]. Several studies reported a high incidence of obesity, ranging between 30 and 40%, in patients with either classic or nonclassic CAH [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that metabolic abnormalities in people with CAH are a consequence of the cortisol deficiency, with the subsequent androgen excess [ 58 ], hypercortisolism related to the GC treatment, which mimics iatrogenic hypercortisolism, as well as the underdevelopment of adrenal medulla [ 11 , 59 , 60 ]. Obesity, which is an independent CV risk factor, is the most frequent component of metabolic syndrome in people with CAH [ 61 ]. Several studies reported a high incidence of obesity, ranging between 30 and 40%, in patients with either classic or nonclassic CAH [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, which is an independent CV risk factor, is the most frequent component of metabolic syndrome in people with CAH [ 61 ]. Several studies reported a high incidence of obesity, ranging between 30 and 40%, in patients with either classic or nonclassic CAH [ 61 , 62 , 63 ]. Interestingly, a significant positive correlation between BMI and serum concentrations of 17-OHP was found in one study [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAH is associated with an increased cardiovascular and metabolic morbidity, likely due to requirement for supraphysiological dose of glucocorticoid to suppress excessive androgen production with glucocorticoids, leading to weight gain, insulin resistance, diabetes, hypertension, dyslipidemia, and general metabolic syndrome. 10 Balancing between glucocorticoid excess and androgen excess and their respective roles in the development of cardiovascular and metabolic comorbidity is of great importance in future improvement of treatment in individuals with CAH. 10,11 A potential link between CAH and cognitive impairments, especially impaired executive functions has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…10 Balancing between glucocorticoid excess and androgen excess and their respective roles in the development of cardiovascular and metabolic comorbidity is of great importance in future improvement of treatment in individuals with CAH. 10,11 A potential link between CAH and cognitive impairments, especially impaired executive functions has been suggested. 12 In addition, an association between CAH and autism spectrum disorder (ASD) traits, such as social communication difficulties and stereotypic behaviours has been described.…”
Section: Introductionmentioning
confidence: 99%